2007
DOI: 10.1902/jop.2007.070072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjunctive Systemic Azithromycin With Periodontal Surgery in the Treatment of Chronic Periodontitis in Smokers: A Pilot Study

Abstract: Background-Along with conventional surgical therapy, systemic antibiotics may provide more effective treatment in smokers by targeting tissue-invasive bacteria. The aim of this randomized, placebo-controlled, double-masked clinical trial was to evaluate the adjunctive effects of systemic azithromycin (AZM) in combination with periodontal pocket reduction surgery in the treatment of chronic periodontitis in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 49 publications
0
121
0
2
Order By: Relevance
“…Similar data have been reported, in chronic periodontitis patients, showing that clinical success may be achieved by adjunctive azithromycin, although little impact on the periodontal microbiota is observed. [16][17][18][19]28 Using the benzoyl-DL-arginine-naphtylamine (BANA) test, Dastoor et al 17 reported no significant difference between azithromycin and placebo groups regarding the reduction in the red complex at any time point. Interestingly, Gomi et al 18 showed that pathogenic bacteria rebounded after 13 weeks of followup, and no significant differences between test and control groups were observed.…”
Section: Act Inomycesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar data have been reported, in chronic periodontitis patients, showing that clinical success may be achieved by adjunctive azithromycin, although little impact on the periodontal microbiota is observed. [16][17][18][19]28 Using the benzoyl-DL-arginine-naphtylamine (BANA) test, Dastoor et al 17 reported no significant difference between azithromycin and placebo groups regarding the reduction in the red complex at any time point. Interestingly, Gomi et al 18 showed that pathogenic bacteria rebounded after 13 weeks of followup, and no significant differences between test and control groups were observed.…”
Section: Act Inomycesmentioning
confidence: 99%
“…14 Studies evaluating the effect of azithromycin on the periodontal microbiota of ChP showed inconsistent findings. [15][16][17][18][19] We previously have demonstrated that azithromycin has the potential to improve periodontal health of young AgP patients when used in combination with scaling and root planing (SRP). 20 To the best of our knowledge there are no published studies evaluating the effects of azithromycin on the periodontal microbiota of young subjects with AgP.…”
Section: Introductionmentioning
confidence: 99%
“…En el presente estudio se encontró que ambos grupos mostraron una disminución de la profundidad al sondaje y ganancia de inserción clínica, sin embargo no se encontró diferencias estadísticamente significativas entre los grupos de azitromicina y el grupo placebo (p>0.05), resultados que coinciden con los encontrados con Han y col, 2 Dastoor y col. 22 y Smith y col. 23 quienes también evaluaron los mismos parámetros clínicos por un periodo de 6 meses y además realizaron estudios microbiológicos donde se evidenció una disminución de microorganismos periodontales en ambos grupos pero sin mostrar diferencias significativas.…”
Section: Discussionunclassified
“…Longer half-life (t 1/2 ) of azithromycin aids increased dosing interval and decreased the course of treatment. Further azithromycin exerts post antibiotic effect conferring longer protection to oral cavity [21]. On the other hand, metronidazole is widely used in periodontal therapy since organisms associated with periodontal infection are often gram negative anaerobes.…”
Section: Effect Of Oral Azithromycin and Metronidazole On Dental Paramentioning
confidence: 99%